BILATERAL SIMULTANEOUS VIDEO-ASSISTED LUNG RESECTION USING A UNILATERAL ACCESS IN TUBERCULOSIS PATIENTS - V. A. Karnaukhov; D. V. Krasnov (Туберкулез и болезни лёгких)
Goal of the study: to compare two surgical tactics for the treatment of bilateral pulmonary tuberculosis.Materials and methods: 189 patients with tuberculous lesions in both lungs underwent lung resections: 91 patients had it done simultaneously on both lungs from the unilateral intercostal-mediastinal access by video-assisted thoracoscopy; 98 patients had resections of the left and right lung done one after another, time period between resections made 20.8 ± 9.4 days on the average.Results. When comparing two tactics – simultaneous bilateral lung resection from a unilateral access and bilateral consecutive resections the following results were obtained respectively: 100 and 96.9% of patients had sputum conversion (p = 0.09, χ2); 100 and 93.8% of patients had healing of lung cavities (p = 0.11, χ2 ). During simultaneous surgery, the risk of intra-operative blood loss exceeding 300 ml was much lower (OR = 9.94; 95% CI 8.60-11.28) as well as the risk of postoperative complications (OR = 2.11; 95% CI 1.89-2.33).